2013
DOI: 10.1088/1674-4527/13/3/002
|View full text |Cite
|
Sign up to set email alerts
|

The gamma-ray Doppler factor determinations for a Fermi blazar sample

Abstract: Observations suggest that γ-ray loud blazars are strongly beamed. The Fermi mission has detected many of blazars, which provide us with a good opportunity to investigate the emission mechanism and the beaming effect in the γ-ray region. We compiled the X-ray observations for 138 Fermi blazars (54 flat spectrum radio quasars, 36 low-peaked BL Lacertae objects, and 48 high-peaked BL Lacertae objects) and calculated their Doppler factors, δ γ. It is interesting that the calculated Doppler factors, δ γ , are stron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
56
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(60 citation statements)
references
References 50 publications
4
56
0
Order By: Relevance
“…A slight higher than our present result if we choose T = 6 h and smaller while T = 48 h is considered (see also Fan et al 2014). For the sake of simplicity, we adopt T = 24 h in this paper for calculation as did in Dondi & Ghisellini (1995), Fan et al (2013a), and Fan et al (2014). Besides, the non-simultaneous observations will also result in some discrepancies.…”
Section: Comparison With Other Doppler Factors In the Literaturementioning
confidence: 55%
See 2 more Smart Citations
“…A slight higher than our present result if we choose T = 6 h and smaller while T = 48 h is considered (see also Fan et al 2014). For the sake of simplicity, we adopt T = 24 h in this paper for calculation as did in Dondi & Ghisellini (1995), Fan et al (2013a), and Fan et al (2014). Besides, the non-simultaneous observations will also result in some discrepancies.…”
Section: Comparison With Other Doppler Factors In the Literaturementioning
confidence: 55%
“…This is consistent with Dondi & Ghisellini (1995), they found the average value δ γ ∼ 4.4, ranging from 1.3 to 11 for a sample of EGRET blazars. Fan et al (2013a) obtained an average value δ γ ∼ 7.22 for 138 γ-ray blazars and Fan et al (2014) also found the average value was ∼7.00 with regard to their sample.…”
Section: Comparison With Other Doppler Factors In the Literaturementioning
confidence: 84%
See 1 more Smart Citation
“…The calculation of γ-ray opacity Doppler factors is based on the requirement that the γ−ray emission region must be transparent to gamma rays (Mattox et al 1993;Fan et al 2013Fan et al , 2014. The process responsible for γ-ray absorption is pair production due to the interaction between γ-ray photons and X-ray photons.…”
Section: Gamma-ray Opacity Doppler Factorsmentioning
confidence: 99%
“…Blazars represent a very special subclass of active galactic nuclei (AGNs) with luminous brightness, rapid and high amplitude variability, high and variable polarization, superluminal motion, strong γ-ray emission, etc (Fan et al 2013, and references therein). In turn, blazars can be divided into two subclasses, namely flat spectrum radio quasars (FSRQs) and BL Lacertae objects (BL Lacs).…”
Section: Introductionmentioning
confidence: 99%